Features of the Immune Response in Infants and Preschool Children with Diabetes Mellitus Type I Against Herpes Virus Infection - G.S. Senatorova; O.P. Pomazunovska; N.V. Shulga (Zaslavsky O.Yu., 2013)
The article presents data on the clinical and laboratory features of the immunological response in children depending on the presence of herpes virus infection. All the children were divided into 3 groups: I group - children with newly diagnosed diabetes mellitus type I, II group - children who are infected with herpes viruses (cytomegalovirus, Epstein-Barr virus, herpes simplex virus type 1, 2; III group - children without viral infection, without signs of diabetes. Based on the observations of the authors, association was established between the appearance of specific antibodies to glutamic acid decarboxylase in children infected with herpes, and increased levels of immunoglobulin G to herpes virus infection. The findings reveal another way to prevent the development of diabetes.